Optimal government size and economic growth in Spain. Evidences through the Armey Curve (1980-2016). - Navarro, Carlos (Advances in Social Sciences Research Journal, 2019)
This study analyzes the effect of public expenditure on economic growth for the Spanish economy, in the period between 1980 and 2016. The Armey curve is used as an analytical tool to describe the relationship between the two variables indicated. The two objectives of this study are check if there is a quadratic relationship of this kind between the two variables for the Spanish economy, as predicted by the model, and there, calculate their optimum. The empirical findings indicate the existence of a significant relationship inverted U-shaped between the two variables in the Spanish economy, obtaining an optimal public expenditure in Spain of 40.07% of GDP, 5.07% lower than the size of the public sector by 2016. Based on these results, an economic policy proposal could be the need to reduce the percentage of public expenditure with the goal of attaining greater efficiency in the Spanish economy.